Multiple active levels in Bi12TiO20 crystals - Freschi, A. A.; Donatti, D. A.; Frejlich, J. (Optical Soc Amer, 2001)
The existence of multiple active levels in a photorefractive Bi12TiO20 crystal is here investigated at 514.5nm wavelength. We carry out two-wave mixing experiments using symmetrically incident beams of equal intensities. A large amplitude fast phase modulation in one of the beams reduces the fringes visibility and improves the detection of the generated frequency modulated signals in both (R and S) output directions. Diffraction efficiencies of the phase (photorefractive) and the absorption (photochromic) gratings are quantitatively computed as functions of the grating period. Results show that the absorption grating has two distinct components: one associated to the photorefractive trap density modulation and another related to local light-induced effects between different levels. The photorefractive grating was also investigated at 633nm and 594nm (besides 514.5nm) and a significant quenching of the photorefractive effect was observed at these wavelengths.